Uznanie dziecka według przepisów Kodeksu rodzinnego i opiekuńczego w świetle regulacji prawa prywatnego międzynarodowego - Uchańska, Joanna (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2012)
The paper discusses the current issues on recognition of paternity in the light of children’s rights. It identifies the proper tools necessary for determining paternity and maternity and highlights their growing importance in connection with common migration and free movement of persons in the EU. The issue of establishing the law applicable to the content or the form of declaration of paternity is presented based on judicial practice. 34 E. Skrzydło-Tefelska, op. cit., s. 149–150.106 | Przegląd Prawniczy Uniwersytetu im. Adama Mickiewicza The paper describes the relationship between recognition of paternity and the process of establishing citizenship and the conditions that must be fulfilled to obtain legal residence in Poland. The conclusions de lege ferenda call for changes in the acquisition of Polish citizenship by operation of law by a child who has been recognized by a man of Polish citizenship. Currently, this possibility is limited by the annual date on which it is necessary to recognize to change a citizenship of a child by law.
Recognition of paternity in the light of the Family and Guardianship Code and international private law
Keywords: prawa dziecka; Kodeks rodzinny i opiekuńczy; prawo prywatne międzynarodowe